From public administration to public governance - Izdebski, Hubert (Journal of Public Governance, 2017)
The study presents the sense of evolution of thinking on public administration – from a legal approach caracteristic of the Rechtsstaat and furher approaches linked with theory of organisation (though the first of them, Woodrow Wilson’s Study of Administration was declared to belong to political science) to present ideas of public governance, oriented on civil society and public administration stakeholders. The subsequent approaches of public administration have not been breaking fully with the previous ones and their implementations, but they have been a kind of „layers”, laid one after another one, and producing the present vision of public administration.